Review of the Literature on Current Changes in the Timing of Pubertal Development and the Incomplete Forms of Early Puberty - Farello, Giovanni; Altieri, Carla; Cutini, Maristella; Pozzobon, Gabriella; Verrotti, Alberto (Frontiers in Pediatrics, 2019)
Abstract Puberty is a sensitive period of life characterized by the appearance of secondary sex characteristics which leads to a complete sexual maturation. It physiologically starts between the age of 8 and 13 years in girls and 9 and 14 years in boys. In the last two decades several studies has showed that start of puberty has moved up to younger ages by 12-18 months and some of the hypothesis trying to explain this change include the role of nutritional status and obesity and the influence of extrinsic factors such as the exposure to the endocrine - disrupting chemicals (EDCs), too. The hypothalamic – hypophysis- gonadal axis develops during embryogenesis, and except for period of activation immediately after birth, remain suppressed until the onset of puberal development. At the beginning of puberty, the pulse generator is reactivated, probably due to progressive stimulatory influeces on GnRH neurons from glial signal and neurotrassitters. Kisspepin and its receptor play a fundamental role in this phase. Premature Pubarche / Adrenarche, Premature Thelarche, Premature Menarche are incomplete form of precocious pubertal development that have their origin in endocrine mechanisms that are only now beginning to be understood. It is important to distinguish these form from the complete ones in order to reassure patients and parents about the non- evolution of pubertal progression and avoiding non-useful treatments with analogous LHRH.